Preparation of Ratharoga Treating Oil Mentioned in Traditional Medical System, and Screening of it for selected Phytochemicals - Pabasara, H.P.M.N.; Munasinghe, D.A.L.; Kalawana, O.T.M.R.K.S.B.; Dahanayaka, J.M. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Ratharoga is a skin disease which mainly occurs in infants and children. This study which was carried out in the Faculty of Indigenous Medicine during May to September 2024, aims in the preparation of one of the Ratharoga treating oil mentioned in traditional medical system, and screening of it for selected phytochemical studies. And also, to make a theoretical analysis of pharmacological action of phytochemicals found, on healing effect. The Ratha thaila recipe mentioned under the Thaila pancha shathakaya hevath beheth thel potha was used here. The oil was prepared according to Traditional medical system. Then it was tested for physicochemical and qualitative phytochemical screening. Prepared oil was; dark green in color, oily as well as bit rough in texture, bitter in taste and pleasant aromatic in odour. Physicochemical wise the pH, refractive index and density were 6.5, 1.46061 (68%) and 0.8375 gml-1 respectively. When considering of the ingredients of the oil, it comprises Pitta shamaka, Raktha shodhaka, Tvachya, Shothahara, Kushtaghna, Krimighna, Vishaghna actions at a higher ratio owing to their Rasa, Guna, Veerya and Vipaka. Phytochemical tests which were carried out with methanol extract, proved that the oil contains tannins, alkaloids and flavonoid. As per modern sciences these phytochemicals are having remarkable physiological and pharmacological properties such as anti - inflammatory, antimicrobial, antioxidants and antiulcer. As the Ratha thaila has been used therapeutically since ancient time, it can be tested further and developed according to the modern technology as high effective product. Thus, the outcome of the study will be a good platform for the researchers who interest on this.
Keywords: Ratharoga; Ratha thaila; Phytochemical analysis